Detection of antibodies to influenza virus M protein by an enzyme-linked immunosorbent assay. - Khan, M W (1982)
An enzyme-linked immunosorbent assay test system was developed in which purified influenza virus M protein was used for the detection of M antibody in human sera. Antibody levels to influenza A virus M protein were monitored in sera from a vaccine study population by using an enzyme-linked immunosorbent assay technique with purified M protein as the adsorbent antigen. A 10-fold variation in titers of preexisting M antibody was observed in this population of young adults. Increases of anti-M titer of 7- to 24-fold were observed upon immunization with Formalin-inactivated vaccine or after natural infection. The antibody response to M protein was dissociated from the response to the hemagglutinin or neuraminidase antigens. The M antibody response preceded or was coincident with the antibody response to H1 hemagglutinin upon natural exposure to circulating virus.